Lights, Camera, Action! English learning through drama - Becerra Carvajal, Wendy Gorena; Alfonso Colmenares, Daniela Lucia; Forero Gómez, Brayan José; Barón Beltrán, Lina Katherine (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Over the past few years, learning English has gained significant importance throughout Colombia. In order for students to accomplish proficiency in this language, different strategies and methodologies are used to help improve their basic language skills. This article explores the use of drama as a strategy to develop two basic English language skills: reading and speaking. Additionally, social relationships among eleventh graders at a public institution are examined. Values, such as leadership, and the use of voice, body language, concentration, and shyness displayed during the activities were analyzed among the students. The most relevant findings form this experience are presented and described as a way to encourage teachers and students to think of drama as a useful pedagogical strategy applicable not only in linguistics, but in social and personal fields as well.